2012
DOI: 10.6002/ect.2011.0117
|View full text |Cite
|
Sign up to set email alerts
|

QT Intervals in Patients Receiving a Renal Transplant

Abstract: Objectives: Cardiovascular disease is the mostcommon cause of mortality in patients with endstage renal disease and renal transplant. Prolongation of QTc max and QTc dispersion are risk factors of cardiac arrhythmias and mortality. This study compares the changes of QT parameters before hemodialysis, after hemodialysis, and after renal transplant. Materials and Methods: Patient candidates for renal transplant were selected. Mean serum electrolyte and 12-lead electrocardiogram were recorded (1) immediately, (2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 27 publications
0
12
1
Order By: Relevance
“…They showed reduction of QTc interval after successful renal transplantation. However, the posttransplant QTc intervals were measured only 2 weeks after the transplantation and obviously this finding do not reflect the potential impact of long‐term exposure to immunosuppressive drugs on QTc intervals . In contrary to those findings, our study revealed that the QT interval prolongation is highly prevalent in the long‐term follow up of kidney transplant patients.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…They showed reduction of QTc interval after successful renal transplantation. However, the posttransplant QTc intervals were measured only 2 weeks after the transplantation and obviously this finding do not reflect the potential impact of long‐term exposure to immunosuppressive drugs on QTc intervals . In contrary to those findings, our study revealed that the QT interval prolongation is highly prevalent in the long‐term follow up of kidney transplant patients.…”
Section: Discussioncontrasting
confidence: 96%
“…QT abnormalities are already commonly encountered in chronic renal patients, particularly in patients undergoing dialysis, and possess an increased risk of cardiovascular mortality . Renal transplantation improves cardiac function and eventually confers a survival benefit in patients with renal disease.…”
Section: Discussionmentioning
confidence: 99%
“…Kidney transplantation can correct electrolyte abnormalities, reverse myocardial remodeling and improve autonomic nerve function, which may be related to QT interval shortening in CKD patients [94,95]. However, the QT interval was measured only after two weeks, and the effect of immunosuppressive drugs on the QT interval was not assessed [96]. In one study, QT interval prolongation was caused by immunosuppressive drugs (tacrolimus, cyclosporine A, everolimus and azathioprine) in the long-term follow-up of kidney transplant patients [23].…”
Section: Drugsmentioning
confidence: 99%
“…In addition to the differences between individuals in measuring QT values and its distribution, the amount of the Nepalese Heart Journal 2018; 15(2): [15][16][17][18][19] values is also affected by sinus arrhythmia and a significant difference is observed after correcting the QT value based on the heart rate and using Bazett's Formula in people with such arrhythmias 33,39,40 . Increases in parasympathetic tone and deceases in the sympathetic tone are associated with prolongation of QTc values, but there is a controversy over its effect on QTd values 41 . It has been evident that the disruption of the autonomic nervous system is associated with increased QTd in diabetics and patients with primary autonomic disorders 26 .…”
Section: Discussionmentioning
confidence: 99%